Global risk mapping for major diseases transmitted by Aedes aegypti and Aedes albopictus. (February 2018) - Leta, Samson; Beyene, Tariku Jibat; De Clercq, Eva M.; Amenu, Kebede; Kraemer, Moritz U.G.; Revie, Crawford W.
Highlights: Despite the fact that many arboviral diseases share the same vectors and often coexist, previous studies have focused on mapping the distribution of one or two diseases separately. In the present study, data from publicly available sources on the occurrence of major arboviral diseases (Zika, dengue fever, chikungunya, yellow fever, and Rift Valley fever) have been compiled and spatially mapped. The risk mapping indicated multiple occurrences of arboviral diseases, with 49% (123/250) of countries reporting two or more diseases in common. The maps include data on vector suitability and disease occurrence to provide decision-makers with a more complete picture when considering coordinated prevention and control programmes. Recognizing that arboviral diseases have common vectors and transmission features, the risk maps can be used to plan interventions in a cost-effective manner. Abstract: Objectives: The objective of this study was to map the global risk of the major arboviral diseases transmitted by Aedes aegypti and Aedes albopictus by identifying areas where the diseases are reported, either through active transmission or travel-related outbreaks, as well as areas where the diseases are not currently reported but are nonetheless suitable for the vector. Methods: Data relating to five arboviral diseases (Zika, dengue fever, chikungunya, yellow fever, and Rift Valley fever (RVF)) were extracted from some of the largest contemporary databases and paired with data on the known distribution of their vectors, A. aegypti and A. albopictus . The disease occurrence data for the selected diseases were compiled from literature dating as far back as 1952 to as recent as 2017. The resulting datasets were aggregated at the country level, except in the case of the USA, where state-level data were used. Spatial analysis was used to process the data and to develop risk maps. Results: Out of the 250 countries/territories considered, 215 (86%) are potentially suitable for the survival and establishment of A. aegypti and/or A. albopictus . A. albopictus has suitability foci in 197 countries/territories, while there are 188 that are suitable for A. aegypti . There is considerable variation in the suitability range among countries/territories, but many of the tropical regions of the world provide high suitability over extensive areas. Globally, 146 (58.4%) countries/territories reported at least one arboviral disease, while 123 (49.2%) reported more than one of the above diseases. The overall numbers of countries/territories reporting autochthonous vector-borne occurrences of Zika, dengue, chikungunya, yellow fever, and RVF, were 85, 111, 106, 43, and 39, respectively. Conclusions: With 215 countries/territories potentially suitable for the most important arboviral disease vectors and more than half of these reporting cases, arboviral diseases are indeed a global public health threat. The increasing proportion of reports that include multiple arboviral diseases highlights the expanding range of their common transmission vectors. The shared features of these arboviral diseases should motivate efforts to combine interventions against these diseases.